The Impact of Children’s Pre-Adoptive Traumatic Experiences on Parents - Skandrani, Sara; Harf, Aurélie; El Husseini, Mayssa’ (Frontiers in Psychiatry, 2019)
For the last decade, children are adopted increasingly at an older age. Their pre-adoptive past can bare traumatic experiences consequent to abandonment, violence or deprivation in birth family or orphanage. The objective of this study is to explore the impact of the child’s traumatic past on parental representations and subsequent parent-child interactions. The study includes 41 French parents who adopted one or more children internationally. Each parent participated to a semi-structured interview, focused on the choice of country, the trip to the child’s native country, the first interactions with the child, the knowledge of the child’s pre-adoptive history.The interviews were analyzed according to a qualitative phenomenological method, the Interpretative Phenomenological Analysis. Five themes emerged from this analysis : absence of affects in the narrative; denial of the significance of the child’s traumatic experiences; perceptions of the uncanny concerning the child; parental worry about traumatic repetition for the child; specific structure of the narrative. These extracted themes reveal a low parental reflective function when the child’s past is discussed. They highlight the impact of the child’s traumatic past on parents. Exploring the impact of the child’s traumatic experiences on adoptive parents enables professionals involved in adoption to provide an early support to these families and to do preventive work at the level of parental representations and family interactions.